Contemporary problems of budget development of regional centers - M. A. Pechenskaya (Russian Journal of Economics and Law)
Objective: to identify the key trends in the development of regional centers’ budgets in 2011-2018 by the example of the North-Western federal district compared to general Russian trends.Methods: system approach, comparison method, horizontal and vertical analysis of financial coefficients, synthesis. Results: territorial development plays the key role in ensuring sustainable development and improving socio-economic indicators in the country. However, it is impossible without the appropriate resource base of the authorities, necessary for the implementation of strategic objectives for the territories’ development. The current system of inter-budgetary relations has led to a significant reduction in the territories’ revenues and a reduction in their budget opportunities. The article identifies the key trends and current development patterns of budget systems of the North-Western federal district regional centers for2011-2018. It is determined that the ratio of own income and gratuitous financial assistance has changed since 2014. Based on the official statistics, it is proved that the key reason for changing the structure of regional centers’ budget revenues is the reduction of revenues from the budget-forming tax on personal income due to legislative adjustments to the mechanism for redistributing tax deductions between the levels of the budget system. The increase in the level of debt burden of the North- Western federal district regional centers from 33 to 52 % of their own revenues was revealed. It is shown that the risk of budget reduction in the social sphere and economy financing increased due to the growing cost of servicing municipal debt, which in the North-Western federal district regional centers increased 14 times in 2011-2018, while the average growth in Russia in that period was four-fold. The increase in the rate of budget expenditures centralization was revealed, which was manifested in an eight-fold increase in the delegated authority from higher levels to the budgets of regional centers of the North-Western federal district in 2011-2018.Scientific novelty: modern patterns of budget systems development of regional centers of Russia and the North-Western federal district are defined and justified, in particular for 2011-2018.Practical significance: the materials of the article can be used by professors of higher educational institutions in the educational process, and by researchers as a research base. Also, the results of the study can be taken into account when implementing the budget process at the municipal level.